Effect of Lattice Structure of Bismuth Sesquioxide on the Electrochemical Energy Storage Characteristics. (19th June 2018) - Day, Brandon C; Kersten, Bethany R; Zillinger, James; Raja, Krishnan S.; Utgikar, Vivek
Abstract : Bismuth oxides have been researched over the last several years due to its low cost compared to other metal oxides. During our experiments two methods were researched to improve the performance of Bi2 O3 for supercapacitance capabilities. One method was using an electrodeposition technique to deposit the bismuth sesquioxide onto ITO glass, another was creating Bi2 O3 powder and pressing it into a Ni foam substrate. For electro-deposition method, α phase showed the highest capacitance of 2027 F/g when calculated from cyclic voltammetry, while charge discharge cycles it was 24 F/g. Ni foam powder ß phase had the greater capacitance of 2559 F/g for cyclic voltammetry and charge discharge was 56 F/g.